Editorial: Empowering Teacher Professionalization with Digital Competencies - Charlott Rubach; Rebecca Lazarides (Education Sciences)
As digital technologies continue to reshape education, equipping teachers with digital competencies has become a pressing need in both policy and research across Europe and worldwide [...]